2011
DOI: 10.1667/rr2517.1
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Cytoglobin Expression Sensitizes Human Glioma Cells to Radiation and Oxidative Stress

Abstract: Cytoglobin is a recently identified vertebrate globin whose functions include scavenging reactive oxygen and nitrosative species. In tumor cells, CYGB may function as a tumor suppressor gene. Here we show that knockdown of cytoglobin expression can sensitize human glioma cells to oxidative stress induced by chemical inhibitors of the electron transport chain and as well can increase cellular radiosensitivity. When treated with antimycin A, an inhibitor of the mitochondrial electron transport chain, cytoglobin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
5
22
1
1
Order By: Relevance
“…Our in vitro loss-and gain-of-function studies using C2C12 myoblasts reflect Cygb's ability to influence cellular redox signaling, with depletion of Cygb increasing ROS generation and sensitizing the cells to stress-induced apoptosis. These findings are consistent with similar loss-and gain-offunction studies demonstrating the ability of Cygb, Mb, or their neuron-specific relative neuroglobin to provide cytoprotection under conditions of oxidative stress (29)(30)(31)(32)(33)(34)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Mutation of the heme-binding domain of Cygb disrupted its ability to confer protection in vitro, demonstrating that Cygb function in this context depends on this core protein structure, a feature common to all globin proteins, and not on a domain unique to Cygb.…”
Section: Discussionsupporting
confidence: 86%
“…Our in vitro loss-and gain-of-function studies using C2C12 myoblasts reflect Cygb's ability to influence cellular redox signaling, with depletion of Cygb increasing ROS generation and sensitizing the cells to stress-induced apoptosis. These findings are consistent with similar loss-and gain-offunction studies demonstrating the ability of Cygb, Mb, or their neuron-specific relative neuroglobin to provide cytoprotection under conditions of oxidative stress (29)(30)(31)(32)(33)(34)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Mutation of the heme-binding domain of Cygb disrupted its ability to confer protection in vitro, demonstrating that Cygb function in this context depends on this core protein structure, a feature common to all globin proteins, and not on a domain unique to Cygb.…”
Section: Discussionsupporting
confidence: 86%
“…The antioxidant effects of CYGB have recently been investigated, and emerging evidence has demonstrated a protective role of CYGB against oxidative stress, especially in models of fibrosis that involve hypoxic reperfusion and subsequent oxidative injury (19, 25, 50 -53). It was also reported that CYGB expression protected neuronal cells from oxidative damage in vitro (21,22,54,55); however, it is unclear whether this is a direct antioxidative effect of CYGB under HI conditions. Downstream signaling in the CYGB pathway may result in these antioxidative effects.…”
Section: Discussionmentioning
confidence: 98%
“…oping and adult brain (20) and is protective under oxidative stress in cell lines (21,22). More recently, Cygb was found to act as a tumor suppressor gene (23,24), and protect kidney fibroblasts under ischemic conditions (25), which are related to oxidative stress (25)(26)(27).…”
mentioning
confidence: 99%
“…We have previously reported that Ngb and Cygb are expressed in human GBM cell lines (18)(19)(20), as well as in human primary tumors including brain tumors (19). In this study, we examined whether hemoglobins (α, β, γ, δ, ζ and ε) are also expressed in human GBM cell lines.…”
Section: Introductionmentioning
confidence: 99%